The Role of Communication and Information Technology in the Health Care Providing Office - Monea, Monica; Pop, Anca Maria; Peter, Olah (European Scientific Journal, ESJ, 2016)
Health informatics technology includes the information technology and electronics employed during medical care procedures and is generally known as clinical informatics. The definition of this specialty was given by the American Medical Information Association in order to describe the role of communication systems in improving the doctor-patient relationship and the quality of medical care. The aim of our investigation was to evaluate the frequency of computer based methods use by medical personnel during daily basic activities in a private dental office. An original questionnaire was sent to a target group of 200 dentists with private dental practice from MureÈ™ County, Romania, with an age between 30-55 years with a private practice opened for at least 2 years. For statistical analysis we used SPSS (Statistical Package for Social Science, version 10.1). The evaluation of results showed that dental software is considered by the majority of respondents to have an important role in improving the quality of medical act and elimination of time consuming procedures.